Efficacy of mindfulness-based cognitive therapy on resiliency and blood glucose control in patients with type II diabetes: Mindfulness-based cognitive therapy in diabetes - Alinezhad, Maedeh; Pourasghar, Mahdi; Hassanzadeh, Ramazan (Chronic Diseases Journal, 2023)
BACKGROUND: Mindfulness-based cognitive therapy (MBCT) training has positive effects on the resilience and blood sugar control in people with type 2 diabetes (T2D). This study aimed to investigate the efficacy of MBCT on resiliency and blood glucose control in patients with T2D. METHODS: This study was a quasi-experimental pretest-posttest with control group. The study population consisted of all patients with T2D in 2018 referring to diabetes clinic of Imam Khomeini Hospital in Sari County, Iran. The sample consisted of 30 (15 for each group) patients with T2D that were selected by availability sampling method and randomly recruited to each of the groups. Next, the experimental group members took part in a total of 8 sessions of 90 minutes each, with one session per week, for MBCT. Instruments for gathering data were the Connor-Davidson Resilience Scale and hemoglobin A1C (HbA1c) test. The data were analyzed with the use of SPSS software and statistical tests such as multivariate analysis of covariance (MANCOVA) and analysis of covariance (ANCOVA). RESULTS: The MBCT had a significant impact on resiliency among patients with T2D (P = 0.001, F = 13.828), but the impact of MBCT on blood glucose control was not significant (P = 0.103, F = 2.854). CONCLUSION: It seems that MBCT is an applicable treatment for improving psychological health for patients with T2D.